Predestination and Free Will in Mudejar Polemics: The Kitāb al-Mujādala maʿa-l-Yahūd wa-l-Naṣārā [The book called the disputation with the Jews and the Christians] and its Historical and Intellectual Background. - Colominas Aparicio, Mònica (Medieval Encounters, 2018)
Predestination and free will were two issues widely debated in the Iberian Peninsula during the Middle Ages, and were subject to different interpretations by Muslims, Christians and Jews. A case in point is the Kitāb al-Mujādala maʿa-l-Yahūd wa-l-Naṣārā [The book called the disputation with the Jews and the Christians], a Mudejar polemic of which the only known manuscript was copied in 808 H (= 1405 CE). I use the discussion of predestination and free will to illustrate the polemical use of these two concepts in this treatise. I also examine how the author addresses his discourse to a learned Mudejar audience by placing the acquisition of proper knowledge of philosophy at the center of the debate. This article uses examples from the Kitāb al-Mujādala to argue that the author's worldview is not exceptional but seems to be connected with that of contemporary Christians and Jews. Moreover, it is indebted to the legacy of Almohad thought among Muslims living in the Iberian Peninsula.